Day 2 Wed, February 05, 2020 2020
DOI: 10.2118/199748-ms
|View full text |Cite
|
Sign up to set email alerts
|

Proppant Flowback: Can We Mitigate the Risk?

Abstract: We propose a new model and workflow to predict, quantify and mitigate undesired flowback of proppant from created hydraulic fractures. We demonstrate several field cases in which we predict significant proppant flowback and propose options for mitigation. Mitigation of proppant flowback is based on case- specific changes in the fracturing treatment design and modifications in the well startup schedule that preserve near-wellbore conductivity. The presented workflow integrates four key components of proppant fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Figure 17 shows the shape of the sand bank before and after flowback with different fiber lengths. The calculated CRs under different fiber lengths (3,6, and 12 mm) are 0.38, 0.34, and 0.29, respectively, which indicate that the proppant pack becomes more resistant to fluid action with the increase of fiber length.…”
Section: Effect Of Different Fibermentioning
confidence: 93%
See 1 more Smart Citation
“…Figure 17 shows the shape of the sand bank before and after flowback with different fiber lengths. The calculated CRs under different fiber lengths (3,6, and 12 mm) are 0.38, 0.34, and 0.29, respectively, which indicate that the proppant pack becomes more resistant to fluid action with the increase of fiber length.…”
Section: Effect Of Different Fibermentioning
confidence: 93%
“…Related studies have shown that the average gas production decline rate of proppant backflow gas wells is more than 3 times that of normal production wells. 3 In addition, the accumulation of backflow proppants at the bottom of the well buries the gas layer or causes erosion of surface pipelines when it is discharged from the wellhead, and so on, which poses safety hazards in construction and production. 4,5 Therefore, the study of proppant backflow is of great significance for the development and production of gas wells.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical model of a hydraulic fracture [17] is the key component of the simulator and incorporates both hydrodynamical and geomechanical aspects of the problem. Fluid flow relative to the proppant pack inside the fracture is governed by the Darcy law.…”
Section: General Simulator Descriptionmentioning
confidence: 99%
“…We were 425 prescribing different critical velocity or, equivalently, different critical flow rate for each fracture in the range from 3.3 bbl/day to 87.0 bbl/day. In the numerical model, we coupled the model of the transient flows in a well, described in [22], with the numer-430 ical models of individual fractures [23]. Each fracture was represented by a grid of conductive cells with fixed width simulating a porous medium.…”
Section: Numerical and Analytical Simulationsmentioning
confidence: 99%
“…The well and fracture models were coupled using iterative algorithm based on Picard iterations (or fixed point itera-440 tions method) [25] that ensured balance of pressures and flow rates between them within certain tolerance. More detailed description of the numerical model and its application to simulation of the cascading failure problem can be found in [23,26]. The problem of pressure-rate coupling 445 between well and fractures has been closely investigated in [27], including study of accuracy and influence of different modifications of algorithm on convergence of fixed point iterations.…”
Section: Numerical and Analytical Simulationsmentioning
confidence: 99%